IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING MODEL ON LIGHT AND OPTICAL DEVICES TOPIC - Syukria, Mila; Oktavia, Rani (SEMESTA: Journal of Science Education and Teaching, 2024)
This study aims to determine the improvement of science learning outcomes of students of SMP Negeri 25 Padang through the application of the Problem Based Learnig (PBL) learning model. The subjects in this study are 33 students. This research is a Class Action Research that refers to the Kemmis and Taggart models. This research was carried out in 3 cycles consisting of planning stages, implementation of actions, observation, and reflection. Research data in the form of cognitive learning outcomes were taken using multiple-choice test and description techniques. The learning outcomes in cycle I were 36.3%, in cycle II it was 72.7%, and in cycle III it was 90.9%. The results of the study show that the Problem Based Learning (PBL) learning model can improve student learning outcomes.